(untitled) (Journal of Nepalese Business Studies, 2007)
This paper attempts to shed light on the new approach of research in finance: clinical approach. This approach is based on these four paradigms: functionalist, interpretative, radical humanist and radical structuralist. The thrust of this paper is to inculcate the concept and paradigms of this new approach of research methodology in the mind of researchers. Journal of Nepalese Business Studies Vol.2(1) 2005 pp.95-98